Consumer Satisfaction with Non-Halal culinary MSMEs at PIK through a Chinese-Themed Atmosphere and Stakeholder Involvement - Cindy Pramita; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardhana (Jurnal of Management and Social Sciences, 2025)
This research employs qualitative and quantitative methods to ascertain the impact of a Chinese-themed atmosphere and stakeholders. The research sample utilized Nvivo and comprised 150 respondents, representing consumers of non-Halal culinary MSMEs at PIK. The research findings demonstrate that the establishment of a Chinese-themed ambiance and stakeholder engagement significantly enhance consumer satisfaction in non-halal culinary MSMEs at PIK, North Jakarta. This amalgamation of methods not only improves the client experience but also generates chances to cultivate customer loyalty and bolster MSME competitiveness. Enhanced execution of stakeholder engagement and ongoing innovation can further propel success in this area.